Peace in Religious Diversity: A Study of Community Inter-Communal Bonds in Thekelan Hamlet Semarang - Grita Gusti Gandi; Diah Kusumaningrum (Jurnal Penelitian, 2020)
This study aims to examine civic engagement through inter-communal ties that occur in one of the hamlets in Indonesia as a representation of a peaceful area. The inter-communal ties that occur in everyday life and are institutionalized show an effort to unite society in diversity. This is important to scrutinize as an applied example for other regions in Indonesia on a small scale about addressing diversity in one region to create peace starting at the grassroots level. The community and religious leaders in Thekelan Hamlet, Batur Village, Getasan District, Semarang Regency, jointly carry out anjangsana activities that can invite the community to unite in commemorating the holidays of each religion in turn. The people of Thekelan Hamlet are a heterogeneous society that adheres to Islam, Buddhism, Christian, and Catholicism. This study uses an ethnographic approach in observing, documenting, and conducting in-depth interviews with informants. The results showed that anjangsana was an institutionalized daily activity. The grassroots community together with religious leaders designed these activities to increase inter-communal ties between communities and maintain peace. The recommendation for further research is to expand the scope of civic engagement studies by analyzing inter-communal ties in regions throughout Indonesia to find appropriate ways to implement peace efforts. The results showed that anjangsana was an institutionalized daily activity. The grassroots community together with religious leaders designed these activities to increase inter-communal ties between communities and maintain peace. The recommendation for further research is to expand the scope of civic engagement studies by analyzing inter-communal ties in regions throughout Indonesia to find appropriate ways to implement peace efforts.